Constrictive Pericarditis After Lung Transplantation - Logan L. Vincent, MD; Siu-Hin Wan, MD; Zachary L. Steinberg, MD; Siddhartha Kapnadak, MD; Rick A. Nishimura, MD; Richard K. Cheng, MD (JACC: Case Reports, 2020)
As a rare complication after lung transplant, cardiac constriction should not be missed. Physical exam, echocardiography, and catheterization are essential for diagnosis A 65-year-old man with previous coronary artery disease and idiopathic pulmonary fibrosis underwent bilateral lung transplant and subsequently presented for progressive dyspnea and volume overload. Cardiac imaging and cardiac catheterization confirmed constriction, and complete pericardiectomy was performed. The patient had rapid resolution of heart failure symptoms. Pericardial constriction is a rare complication following lung transplant, and we provide a review of the literature and discussion of potential contributing factors. (Level of Difficulty: Intermediate.)